2012
DOI: 10.3390/app2030641
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Process for Biodiesel Production in Packed Bed Reactor from Waste Frying Oil Using Potassium Hydroxide Supported on Jatropha curcas Fruit Shell as Solid Catalyst

Abstract: Abstract:The transesterification of waste frying oil (WFO) with methanol in the presence of potassium hydroxide catalyst supported on Jatropha curcas fruit shell activated carbon (KOH/JS) was studied. The catalyst systems were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and the Brunauer-Emmett-Teller (BET) method. The effects of reaction variables such as residence time, reaction temperature, methanol/oil molar ratio and catalyst bed height in packed bed reactor (PBR) on the yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…Most of the essential metallic compounds contained in the raw CAE catalyst were decomposed into their corresponding oxides and carbon dioxide, CO2, after the calcination process (Tan et al, 2015); this left cavities that indicated both the solid rearrangement and exit route of the eliminated components (Leofanti et al, 1997). This result aligns with the findings of Buasri et al (2012), who reported that calcined carbonatederived catalysts are made up of particles with small shapes. …”
Section: Scanning Electron Microscopy (Sem)supporting
confidence: 81%
“…Most of the essential metallic compounds contained in the raw CAE catalyst were decomposed into their corresponding oxides and carbon dioxide, CO2, after the calcination process (Tan et al, 2015); this left cavities that indicated both the solid rearrangement and exit route of the eliminated components (Leofanti et al, 1997). This result aligns with the findings of Buasri et al (2012), who reported that calcined carbonatederived catalysts are made up of particles with small shapes. …”
Section: Scanning Electron Microscopy (Sem)supporting
confidence: 81%
“…The physical and chemical properties of FAME including kinematic viscosity, density, flash point, cloud point, pour point, acid value, and water content were analyzed according to ASTM methods [11]. …”
Section: Methodsmentioning
confidence: 99%
“…Figure shows XRD patterns of the dried apple, carbonized apple and the porous SiC ceramics (obtained at the temperature of 1600 °C). It is observed that dried apple exhibits broad peaks with an absence of any sharp peaks, which demonstrate the amorphous nature of the material . In the XRD pattern of the carbonized apple, the diffraction peaks at 24.5° and 43.7° were assigned to the (002) and (100) planes of graphite, respectively.…”
Section: Resultsmentioning
confidence: 96%